Corporate social responsibility and ambidextrous green innovation: The role of green creativity as mediator - Md. Alauddin (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
This study examines how corporate social responsibility (CSR) affects green creativity (GC) and ambidextrous green innovation (AGI). Using information from 220 manufacturing companies in Bangladesh, this paper investigates the function of green creativity as a mediator in the connection between CSR and green innovation. The data were gathered using survey methods through the convenience sampling technique via covariance-based SEM (CB-SEM). Our findings demonstrate that CSR directly affects innovation in green exploitation and exploration. CSR is more associated with green exploration innovation than green exploitation innovation, and CSR positively correlates with green creativity. The study also found that green creativity acts as a mediator between CSR and ambidextrous green innovation, suggesting that improving CSR initiatives can foster green creativity, which can lead to innovation in green exploration and exploitation. The findings suggest that managers should focus on improving their CSR initiatives to foster green creativity, which can lead to innovation in both green exploitation and green exploration.
Keywords: 330; Corporate social responsibility (CSR); green creativity; green innovation; greenexploration innovation; green exploitation innovation; manufacturing industry; Bangladesh